Improving Learning Outcomes Of Islamic Religious Education Through The Application Of The Project Method For Class Iii Students Of Gresik State Primary School - Khoiroh, Mislakhul; Ladamay, Ode Moh. Arfa (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
They are using commercial tactics to increase their accomplishments in Islamic education in the third year, and learning at Gresik State Elementary School results in enrollment at Gresik State Elementary School. The instructor's way considers this to be a loss of concern for the students, as those who still need to meet the Minimum Completion Criteria are classified as impoverished individuals. In elementary schools, the Strategy Project is a comprehensive initiative that teaches writing, reading, crafts, and other subjects. Over three years at Public Alementary School Gresik, the Project learned Islamic principles by using technology to construct this formula for investigating inner difficulties. This study used a project technique to expand on the findings of three years at Gresik State Elementary School by examining Islamic lessons. The study will be conducted over a number of months, beginning in August 2010 and terminating when it is finished. A study of classroom activities makes up the research structure (classroom Activity Research). The instruments for studying edges and gathering data to update the status of inspection findings are included in this inspection equipment. Cycles I and II yielded the initial test results, which indicated a rise in scores from Cycle I to Cycle II. The learning value gained in the pre-activity outcomes information was 49%. The score climbed by 63% in Cycle I and by 77% in Cycle II. It is clear from the facts above that degree II and degree II learning outcomes and the development of teacher activities are closely related. The existing state of affairs demonstrates how educator activities and second degrees affect second-degree success. The readiness of educators and their replacements to support the growth of activities at the level of learning outcomes keeps things as they are. The findings support the following research conclusions.